ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL CERITA SISTEM PERSAMAAN LINEAR TIGA VARIABEL KELAS X SMA NEGERI 2 TARERAN - Rantung, Natalia Cristina; K.Tumalun, Nicky; Ermita, Ermita (Dharmas Education Journal (DE_Journal), 2024)
This research was motivated by the problems faced by students in solving word problems in the System of Three Variable Linear Equations (SPLTV) material. The data analysis technique used in this research is qualitative descriptive analysis, namely with the steps 1) data collection, 2) data reduction/condensation, 3) data presentation, 4) drawing conclusions. The data collection technique used in the research was a written test in the form of five story questions and interviews with 5 students who were selected based on the type of error made based on the Newman procedure which aims to explore the causes of the error and further identify the error that occurred. The subjects used in this research were all 21 class X (Ten) students. The results of the research concluded that 2.86% of students made reading errors caused by students misreading the numbers or symbols in the problem, 11.43% of students misunderstood the problem which was caused by students not understanding what they knew and asked in the question, the transformation error was 9.52% which was caused by students not knowing how to make an equation into the correct mathematical model, the process skill error was 31.43% which was caused by students not being careful in the process of solving the problem in carrying out the correct calculations. cause the final results obtained to be wrong, and errors in writing final answers amounted to 23.81% which was caused by students not writing conclusions or final answers and also due to incorrect calculations so that the final results were also wrong.